Exploration of Plant Species Used by Bapedi Ethnic Group for Ethnoveterinary Purposes: A Case Study of Ga-Mphahlele Region in the Limpopo Province, South Africa - Sebua Silas Semenya; SekgotheMokgoatšana; Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2019)
The use of plant resources by the Bapedi people in the Limpopo province in South Africa is regarded as part of their tradition and culture. This study was aimed at documenting ethnoveterinary uses of plants in Ga-Mphahlele region in the Limpopo province, South Africa. Information was gathered through semi-structured questionnaires supplemented by field observations from 30 randomly selected Pedi speaking people in Ga-Mphahlele region of the Limpopo province. A total of 52 plant species from 32 plant families were used for 18 ethnoveterinary purposes. The majority of the species (21.2%) were used as fodder, followed by ethnoveterinary medicinal applications against wounds (19.2%), diarrhoea (17.3%), ticks (13.5%) and worms (11.5%) in domestic animals such as cattle, chickens, dogs, donkeys, doves, goats and sheep. The species with frequency of citation (RFC) higher than 0.70 included Citrullus lanatus (fodder), Vachellia karroo (ethnoveterinary medicine and fodder), Sclerocarya birrea subsp. caffra (fodder), Aloe ferox (ethnoveterinary medicine), Drimia sanguinea (ethnoveterinary medicine), Sarcostemma viminale subsp. viminale (ethnoveterinary medicine) and Sorghum bicolor (fodder). The traditional knowledge about forage and ethnoveterinary medicines demonstrated by the Bapedi people enable extension officers and policy makers to appreciate how local communities perceive and utilize plant resources around them.